ANALISIS KARAKTERISTIK SOSIAL EKONOMI DAN PARTISIPASI PETANI SUKU DAYAK KENYAH PADA USAHATANI PADI LADANG (Studi Kasus di Desa Long Anai dan Sungai Bawang, Kabupaten Kutai Kartanegara) - MIDIANSYAH EFFENDI; DINA LESMANA; EKO HARRI YULIANTO; FIRDA JUITA; SARIPAH NURFILAH (Universitas Mulawarman (University of Mulawarman), 2021)
The success of upland rice farming in increasing farmers' income requires high participation in farming management in order to provide optimal results. The purposes of this study were to determine the socio-economic characteristics of farmers, to analyze farming, to determine farmer participation, and to analyze the factors that determine the participation of Dayak Kenyah farmers in upland rice farming. This research was conducted in Long Anai and Sungai Bawang Villages, Kutai Kartanegara District. The characteristics of upland rice farming of the Dayak Kenyah tribe in terms of gender, age, education level, number of family dependents, land area, and income. Upland rice farmers of Dayak Kenyah tribe still apply cultural customs in most stages of upland rice farming. The level of community participation was high and is at the partnership stage. The factors that determine the participation of Dayak Kenyah tribe farmers in upland rice farming are culture, ideas, labor, working time, and farming capital.